Toward laser-induced vibrational emission spectroscopy of C+60. (August 2015) - Kumar, S Sunil; Bizenberger, Peter; Blaum, Klaus; Breitenfeldt, Christian; Göck, Jürgen; Grözinger, Ulrich; Henning, Thomas; Karthein, Jonas; Kern, Bastian; Meyer, Christian; Rouillé, Gaël; Strelnikov, Dmitry; et al.
Synopsis: C + 60 has been proposed to be responsible for two of the diffuse interstellar bands (DIBs), the absorption features observed in the visible-to-near-infrared spectra of the interstellar medium. However, a confirmation requires laboratory gas-phase spectra, which are so far not available. We plan to develop a novel spectroscopy technique that will allow us to obtain the first gas-phase spectra of C + 60, and that will be applicable to other complex organic molecules such as polycyclic aromatic hydrocarbons. The current status of the experimental setup, the ideas behind the measurement scheme and the preparatory work toward its implementation will be presented.